2018
DOI: 10.1016/j.fertnstert.2017.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Low dosing of gonadotropins in in vitro fertilization cycles for women with poor ovarian reserve: systematic review and meta-analysis

Abstract: CRD42016041301.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 45 publications
0
16
0
1
Order By: Relevance
“…Regarding the secondary outcomes of this study, the aforementioned systematic review and meta-analysis found significant lower ovarian stimulation days and significantly more treatment cycles were cancelled due to poor ovarian response in women who underwent MS-IVF than in women who underwent C-IVF, while we found no significant difference (Youssef et al, 2018). They also found no significant differences between groups in the SA1: sensitivity analysis 1, the pregnancy rate per embryo transfer as primary effect outcome (i.e., the number of cycles in which embryos were transferred into the uterus were included in the denominator).…”
Section: Comparison With Other Effectiveness Studiesmentioning
confidence: 44%
See 1 more Smart Citation
“…Regarding the secondary outcomes of this study, the aforementioned systematic review and meta-analysis found significant lower ovarian stimulation days and significantly more treatment cycles were cancelled due to poor ovarian response in women who underwent MS-IVF than in women who underwent C-IVF, while we found no significant difference (Youssef et al, 2018). They also found no significant differences between groups in the SA1: sensitivity analysis 1, the pregnancy rate per embryo transfer as primary effect outcome (i.e., the number of cycles in which embryos were transferred into the uterus were included in the denominator).…”
Section: Comparison With Other Effectiveness Studiesmentioning
confidence: 44%
“…number of oocytes retrieved, the number of MII oocytes, and the number of embryos obtained, while we found significant lower numbers of oocytes retrieved and embryos for the MS-IVF treatment protocol compared to the C-IVF (Youssef et al, 2018). These differences might be related to differences in medication dosages and other differences in populations, such as the underlying causes of infertility.…”
Section: Comparison With Other Effectiveness Studiesmentioning
confidence: 59%
“…23 In our clinic, we use the NC-IVF stimulations for women at risk of OHSS or when the women prefer less hormone or lower price for IVF. The evidence on cycle cancellation is conflicting and some metaanalyses of RCTs showed higher cumulative pregnancy rate with mild IVF [24][25][26][27] while other meta-analyses found no difference. 23,28 One study outlines that affordable ART with low dose stimulation provide a more patient-friendly treatment for many women undergoing fresh IVF treatment cycles because they cause less stress and are more convenient for the patient.…”
Section: Discussionmentioning
confidence: 99%
“…The recent available evidence suggests that, in POR patients, mild OS regimens (low-dose gonadotropins with/without oral agents), when compared with traditional OS protocols, offer comparable reproductive outcome albeit lower cost. 45 , 46 Across all the available studies on DS/DuoStim, different OS protocols have been described for FPS and LPS. Regarding FPS, luteal estrogen priming may be used to promote synchronization and coordination of follicular growth.…”
Section: How To Perform Double/dual Stimulation?mentioning
confidence: 99%